(untitled) (Academicia Globe: Inderscience Research, 2021)
As a result of the ongoing reforms in our independent country, worthy achievements are being made in all spheres of our society. Ensuring a peaceful, peaceful and prosperous life for the people is at the heart of these efforts. Peace begins with the family and the neighborhood. In this regard, in every residential area of the country is held awareness-raising events with the participation of law enforcement officers, district supervisors, community activists, representatives of public organizations.